“Entra, menino”, “Xô, galinha” e “Sim, senhor!”: entrevista com Heloneida Studart - Neckel, Roselane (Revista Estudos Feministas, 2008)
“Entra, menino”, “Xô, galinha” e “Sim, senhor!”: entrevista com Heloneida Studart